The Relationship of Parenting with Physical Independence in Preschool Children - Sugeha, Kirana Aliya Putri; Watung, Grace I.V; Novitasari, Dalia (Omni Health Journal, 2025)
Background: Early childhood is a vulnerable child aged 0 (from birth) to 6 years. This age is often termed as the golden years, which is a very valuable age compared to later ages because the child absorbs all the stimuli he gets. Entering the age of 5-6 years the child begins to develop various abilities and skills in taking care of themselves when the child begins to explore the various skills he has such as learning to walk, eat, interact with others and formation. Understanding and learning morals as a form of early childhood independence. Objective: This study aims to find out how parental parenting and physical independence in preschool children are. Methods: This research method uses a type of analytical research using a cross sectional approach. Results: After the Chi-Square test was carried out, there was a relationship between parental parenting and physical independence in preschool children with a p value of p value = 0.000 or <P = 0.05. Conclusion: Based on the results of the study, it can be concluded that democratic parenting is the most widely applied parenting style by parents in Raudhatul Athfal Nurul Huda, Poyowa Kecil Village, where children with this parenting style are declared physically independent more than other parenting styles.